Retracing African Moral Values and Balancing Afro-Pop Music - Tairu, Abiodun Olukayode; Olayemi, Oluwakemi Titilola; Maraiyesa, Ayokunle, O. (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This study examines the complex relationship between Afro Pop music and traditional African moral values. Through a critical analysis of lyrics, music videos, and artist interviews, this research investigates how Afro-Pop’s increasing commercialization and global influence affects its representation of African cultural norms. The study combines a mixed-methods approach with content analysis and surveys to interrogate the data samples of 16 collected Afro-pop songs. A riveting exposition of respect and modesty versus vulgarity and profanity was juxtaposed to reposition and validate the status of African morality through the festering of Afro Pop Music. The study contributes to the ongoing debates on cultural globalisation, African identity, and the role of music in shaping moral values.